2023
DOI: 10.1088/1755-1315/1192/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Population structures of Pyricularia oryzae Cavara in South Sulawesi

Abstract: Blast disease caused by Pyricularia oryzae is one of the major rice diseases affecting rice output in Indonesia causing a 90% reduction in yield. This study aimed to determine the distribution of Pyricularia oryzae virulence pathotypes (races) in several South Sulawesi regencies. The P. oryzae races were determined in the Green House using 7 rice differential varieties: Asahan, Cisokan, IR 64, Krueng Aceh, Cisadane, Cisanggarung, and Kencana Bali. A total of 72 P. oryzae isolates from Maros, Gowa, Bone, and Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Morphologically, the most typical characteristics of blast disease shown in dryland rice crops are brown spots shaped like rhombuses (Figure 1). Kuswinanti et al (2023) also obtained the same symptom characteristics in Pyryicularia orizae. Other studies also report on the blast disease Pyricularia oryzae, which can attack all rice plant tissues, including leaves, stems, panicles, and grains (Asibi et al 2019), as shown in Figure 1.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Morphologically, the most typical characteristics of blast disease shown in dryland rice crops are brown spots shaped like rhombuses (Figure 1). Kuswinanti et al (2023) also obtained the same symptom characteristics in Pyryicularia orizae. Other studies also report on the blast disease Pyricularia oryzae, which can attack all rice plant tissues, including leaves, stems, panicles, and grains (Asibi et al 2019), as shown in Figure 1.…”
Section: Discussionsupporting
confidence: 53%
“…Blast disease potentially attacks every part of rice organs in the fields (Muimba-Kankolongo 2018). Kuswinanti et al (2023) reported the highest percentage of blast disease attacks in Indonesia found on rice leaves, starting from 5% in the first week and reaching 82.1% at the harvest period. Potential yield losses due to blast disease can reach 50% or more, as reported by Nalley et al (2016), following the next survey in 2021, a field survey conducted in two districts on Lombok Island, including Central Lombok Regency, attacked by blast disease at 70% and North Lombok Regency at 20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation